Monitoring, Evaluation and Learning (MEL) Plan for AICCRA Zambia - Kakwasha, Keagan; Mudege, Netsayi N.; Cullhaj, Megi; Schuetz, Tonya; Siamudaala, Victor (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
This Monitoring and Evaluation and Learning (MEL) Plan for the AICCRA project is a management tool that will help the project track and assess progress and achievements and make adjustments if necessary to ensure that the project can achieve its objectives intended results. The purpose of this MEL plan is: (i) to explain how the project will be monitored to determine whether the intended results are being achieved; (ii) to define the project data sources that will be used to verify the results achieved; (iii) to establish a process to alert implementers and stakeholders of any problems in project implementation and provide the basis for making any needed adjustments; and (iv) to describe information products such as reports and other written documentation that the project will produce and disseminate to its stakeholders, internal and external audiences.